2013
DOI: 10.1371/journal.pone.0059538
|View full text |Cite
|
Sign up to set email alerts
|

Copper Deficiency Leads to Anemia, Duodenal Hypoxia, Upregulation of HIF-2α and Altered Expression of Iron Absorption Genes in Mice

Abstract: Iron and copper are essential trace metals, actively absorbed from the proximal gut in a regulated fashion. Depletion of either metal can lead to anemia. In the gut, copper deficiency can affect iron absorption through modulating the activity of hephaestin - a multi-copper oxidase required for optimal iron export from enterocytes. How systemic copper status regulates iron absorption is unknown. Mice were subjected to a nutritional copper deficiency-induced anemia regime from birth and injected with copper sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 48 publications
4
34
0
Order By: Relevance
“…The BBM ferrireductase CYBRD1 can reduce iron and copper (117), demonstrating a potential point of intersection. Moreover, Matak et al (71) recently reported that CYBRD1 was induced in the intestinal epithelium of copper-deprived mice. The proposed mechanism related to intestinal hypoxia resulting from copper-deficiency anemia and a concomitant increase in CYBRD1 gene transcription mediated by the hypoxia-inducible transcription factor HIF2α.…”
Section: Iron-copper Interactions In Intestinementioning
confidence: 99%
See 1 more Smart Citation
“…The BBM ferrireductase CYBRD1 can reduce iron and copper (117), demonstrating a potential point of intersection. Moreover, Matak et al (71) recently reported that CYBRD1 was induced in the intestinal epithelium of copper-deprived mice. The proposed mechanism related to intestinal hypoxia resulting from copper-deficiency anemia and a concomitant increase in CYBRD1 gene transcription mediated by the hypoxia-inducible transcription factor HIF2α.…”
Section: Iron-copper Interactions In Intestinementioning
confidence: 99%
“…Whether its expression or activity is altered by variations in copper status has been investigated. Copper deficiency in mice was shown to increase FPN1 mRNA expression, possibly by a transcriptional mechanism involving HIF2α (71). Another recent study, however, provided contradictory results (90).…”
Section: Iron-copper Interactions In Intestinementioning
confidence: 99%
“…For the long isoform, there was uniform protein distribution throughout the cytoplasm and appreciable localization in the vicinity of the plasma membrane; in contrast, the protein encoded by the short isoform was largely perinuclear ( Figure 3B). Given the quantitative limitations of immunocytochemistry, we performed biochemical localizations studies, in which we fractionated cells in high sucrose buffer as previously described, 26 purified membrane fractions, and performed immunoblotting either with the Myc tag or with an antibody against Na þ /Kþ ATPase, a membrane marker (Abcam ab7671; 1:10,000 dilution). In this experiment, we observed a striking difference in the relative ratios of long and short protein isoforms in the membrane ( Figure 3C), a result consistent with the observed immunocytochemical distributions.…”
Section: Renal Defectsmentioning
confidence: 99%
“…However, models of intestinal iron overload coupled with systemic anemia indicate that elevated iron levels do not have a pronounced effect on HIF-2 per se and that systemic anemia/hypoxia is the predominant regulator of HIF-2. 74 It would be interesting to examine these hypotheses more specifically in mice with inducible deletion of Irp1 or Irp2 in the intestinal epithelium. Further studies addressing these questions may provide evidence for nonredundant roles of IRPs in the duodenum and their importance in integrating systemic physiological signals in vivo.…”
Section: Posttranscriptional Regulation By the Irps: A New Irp1/hif-2mentioning
confidence: 99%